Cold Ding / Nor Habibah Yahabib - Yahabib, Nor Habibah (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
The name of this product is Cold Ding. This product is a Malaysian ice cream mixed with pudding. Cold is made up of the word cold ice cream. While Ding came from the abbreviated word pudding. This Cold Ding is produced from the idea of Malaysian ice cream because it retains the aspect of ice packing from the past. The customer's name is Naa Aiskrim Malaysia. The product description for this product is Malaysian Ice Cream Pudding. "Cold, Sweet, and Tasty" is a slogan for this product to tell buyers that it has the cool taste of the ice cream and the sweetness and softness of the pudding. This Malaysian ice cream product has been inherited from many years ago. There are many Malaysian Ice Cream products in a market that has a variety of flavours. However, this Cold Ding product has a difference in terms of a name that is rarely heard and a pudding mix that is never sell in the market. In addition, this product has different flavours, namely Strawberry, Oreo, and Jelly. Cold Ding is a new milk and pudding powder product. It is also because it has the calcium nutrients from milk even if it is just a dessert. The strength of this product is liked by many because of its pleasant nature for buyers that is cold eaten and a nutritious dessert. In addition, it can provide satisfaction and enjoyment during the hot weather, as well as cheer up the atmosphere. It's challenging to produce this product. One of them is to have a lot of competiton because Malaysian ice cream is very famous in terms of packaging that everyone knows. In addition, it is still new and unknown to many with a different name. The solution is by making the design more modern and looks exciting for consumer. The target consumers for this product are children, adolescents, and adults, especially families. The most accurate target is ice cream enthusiasts. This product can give joy to anyone who eat it because of its cool, sweet, and soft nature. The idea is the same as other Malaysian ice creams but in terms of packaging and different names because of various flavours in one box and is easy to carry anywhere. It is also available in the box as it is frozen for 12 hours in the refrigerator, after it is cold just eat with the family. In conclusion, the purpose of Cold Ding is to share happiness and restore a pleasant and fresh taste.